Role of the putative sit1 gene in normal germination of spores and virulence of the Mucor lusitanicus - Bernadett Vágó; Kitti Bauer; Naomi Varghese; Sándor Kiss-Vetráb; Sándor Kocsubé; Mónika Varga; András Szekeres; Csaba Vágvölgyi; Tamás Papp; Gábor Nagy (Microbial Cell)
Mucormycosis is a life-threatening infection caused by certain members of the fungal order Mucorales, with increased incidence in recent years. Individuals with untreated diabetes mellitus, and patients treated with deferoxamine are particularly susceptible to this infection. Elevated free iron concentrations in serum contribute to the development of mucormycosis. Pathogenic fungi have evolved multiple mechanisms to acquire and utilize free iron or extract it from the various iron-binding molecules within the host. The utilization of hydroxamate siderophores as xenosiderophores may contribute to the development of mucormycosis. The genome of Mucor lusitanicus encodes one Sit1 siderophore transporter. In this study, the role of the sit1 gene was characterized by generating knockout mutants using CRISPR-Cas9. Relative transcript level of the sit1 gene significantly increased in the presence of deferoxamine- and deferasirox-iron complexes. Lack of sit1 resulted in altered germination of spores and growth ability, and decreased virulence. Furthermore, absence of the gene caused elevated transcript levels of a ferric reductase (FRE), a low-affinity iron permease (FET4) and a copper dependent iron oxidase (FET3). Our result suggests that expressions of the genes involved in iron uptake affect each other. The lack of Sit1 resulted in an increased transcript level of the FRE3 gene, which may be able to reduce iron from the siderophore-iron complex. The reduced and liberated iron may be then taken up by activated FET4a. This study highlights the significance of understanding the iron acquisition mechanisms of pathogenic fungi to develop effective treatments for fungal infections.